Endoscopic Palliation for Biliary and Pancreatic Malignancies: Recent Advances - Zaheer Nabi; D. Nageshwar Reddy (Korean Society of Gastrointestinal Endoscopy, 2019)
Malignancies of the pancreatobiliary system are usually unresectable at the time of diagnosis. As a consequence, a majority of these cases are candidates for palliative care. With advances in chemotherapeutic agents and multidisciplinary care, the survival rate in pancreatobiliary malignancies has improved. Therefore, there is a need to provide an effective and long-lasting palliative care for these patients. Endoscopic palliation is preferred to surgery as the former is associated with equal efficacy and reduced morbidity. The main role of endoscopic palliation in the vast majority of pancreatobiliary malignancies includes biliary and enteral stenting for malignant obstructive jaundice and gastric outlet obstruction, respectively. Recent advances in endoscopic palliation appear promising in imparting long-lasting relief of symptoms. Use of radiofrequency ablation and photodynamic therapy in malignant biliary obstruction has been shown to improve the survival rates as well as the patency of biliary stents. The emergence of endoscopic ultrasound (EUS) as a therapeutic tool has enhanced the capability of minimally invasive palliation in pancreatobiliary cancers. EUS is a valuable alternative to endoscopic retrograde cholangiopancreatography for the palliation of obstructive jaundice. More recently, EUS is emerging as an effective primary modality for biliary and gastric bypass.